2018
DOI: 10.1371/journal.pone.0195415
|View full text |Cite
|
Sign up to set email alerts
|

Increased male bias in eider ducks can be explained by sex-specific survival of prime-age breeders

Abstract: In contrast to theoretical predictions of even adult sex ratios, males are dominating in many bird populations. Such bias among adults may be critical to population growth and viability. Nevertheless, demographic mechanisms for biased adult sex ratios are still poorly understood. Here, we examined potential demographic mechanisms for the recent dramatic shift from a slight female bias among adult eider ducks (Somateria mollissima) to a male bias (about 65% males) in the Baltic Sea, where the species is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…At the larger scale, several single-site studies have rejected winter climate, a large-scale and potentially synchronizing attribute of the environment, as a driver of variation in female survival, but this remains yet to be investigated at the level of multiple colonies of mixed geographical origin (Hario et al, 2009;Ekroos et al, 2012b;Tjørnløv et al, 2013). Finally, spring counts of eiders migrating into the Baltic Sea suggests that the flyway population sex ratio has shifted toward an increasing male bias (Lehikoinen et al, 2008;Berg, 2014;Ramula et al, 2018), which can mainly be attributed to sex-specific survival of prime reproductive-age individuals (≥5-year-old) during the breeding season (Ramula et al, 2018). An evaluation of hunting at the flyway scale suggests that in recent decades hunting has been sustainable and wellregulated (Tjørnløv et al, 2019), ultimately resulting in a ban on hunting females in Denmark (where most hunting takes place) from 2014 onward (Christensen and Hounisen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the larger scale, several single-site studies have rejected winter climate, a large-scale and potentially synchronizing attribute of the environment, as a driver of variation in female survival, but this remains yet to be investigated at the level of multiple colonies of mixed geographical origin (Hario et al, 2009;Ekroos et al, 2012b;Tjørnløv et al, 2013). Finally, spring counts of eiders migrating into the Baltic Sea suggests that the flyway population sex ratio has shifted toward an increasing male bias (Lehikoinen et al, 2008;Berg, 2014;Ramula et al, 2018), which can mainly be attributed to sex-specific survival of prime reproductive-age individuals (≥5-year-old) during the breeding season (Ramula et al, 2018). An evaluation of hunting at the flyway scale suggests that in recent decades hunting has been sustainable and wellregulated (Tjørnløv et al, 2019), ultimately resulting in a ban on hunting females in Denmark (where most hunting takes place) from 2014 onward (Christensen and Hounisen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the between-sex differences in survival observed in our study are of such amplitude to explain the excess of males into the wintering population remains to be properly assessed (using Leslie-Usher matrix modelling for example, Caswell 1980, Ramula et al 2018. Nevertheless, here we Table 3.…”
Section: Survival Probabilities and The Excess Of Males On Wintering mentioning
confidence: 80%
“…It looks much like that of the common eider Somateria mollissima, whose increasing proportion of males originate from differences in survival of prime breeders too (i.e. lower survival of females, Ramula et al 2018). However, unlike Ramula et al (2018), we emphasize that increasing proportions of males recently observed in common pochard in western Europe 1) were possible because adult males displayed higher survival than adult females, but, 2) originated from lowered reproductive success and/or juvenile survival (since survival patterns of adults did no changes over very long periods).…”
Section: Discussionmentioning
confidence: 98%
“…Because staging and wintering areas gather birds from different parts of the breeding range, and the origin of birds usually remains unknown, data from wintering areas are not well suited to the study of specific mechanisms behind changes in sex ratios. Lehikoinen et al (2008) and Ramula et al (2018) studied possible mechanisms that could lead to male-biased adult sex ratios in Common Eiders Somateria mollissima, a seasonally monogamous sea duck. Ramula et al (2018) concluded that, although duckling mortality is female biased and could contribute to male-dominated adult sex ratios (Lehikoinen et al 2008), the most probable explanation of male-biased adult sex ratio in their study populations (central and western Gulf of Finland) is lower survival of females than males among experienced breeders, most likely due to increased predation pressure on incubating females.…”
Section: Introductionmentioning
confidence: 99%
“…Lehikoinen et al (2008) and Ramula et al (2018) studied possible mechanisms that could lead to male-biased adult sex ratios in Common Eiders Somateria mollissima, a seasonally monogamous sea duck. Ramula et al (2018) concluded that, although duckling mortality is female biased and could contribute to male-dominated adult sex ratios (Lehikoinen et al 2008), the most probable explanation of male-biased adult sex ratio in their study populations (central and western Gulf of Finland) is lower survival of females than males among experienced breeders, most likely due to increased predation pressure on incubating females. Similarly, Bellebaum and Mädlow (2015) found in an introduced Mandarin Duck Aix galericulata population in two German cities (Berlin and Potsdam) that higher mortality of females than males in particular during the breeding season can explain male-biased adult sex ratio.…”
Section: Introductionmentioning
confidence: 99%